Students’ Choice Intention of a Higher Learning Institution : An Application of the Theory of Reasoned Action (TRA) (Malaysian Management Journal, 2003)
The purpose of the present study is to identify the determinants of upper secondary level students’ intentions whether to choose a private or a public higher learning institution. Ajzen and Fishbein’s (1980) Theory of Reasoned Action was used as the basis for this study. The theory posits that the immediate determinant of behavior is intention. Intention is determined by the weighted attitude toward the behavior and the weighted subjective norm. Combinations of beliefs, evaluations, and motivation to comply determine attitude and subjective norm towards behavior. Salient beliefs related to attitude towards both private and public institutions of higher learning and salient beliefs related to the subjective norm for both private and public higher learning institutions were identified. The sample consisted of 132 students whose age ranges from 16 years to 24 years. Hypotheses generated in accordance to the theory were confirmed. The findings also showed that attitude toward behavior and subjective norm explained 75% of the variance in behavioral intention for both private and public institutions of higher learning. Attitude toward behavior had a greater relative weight (β =0.539) compared to the subjective norm (β =0.401) for both private and public higher learning institutions. Implications of the above findings are discussed.